PENGARUH PENGGUNAAN METODE PEMBELAJARAN TIPE GROUP INVESTIGATION (GI) DAN TEAMS GAMES TOURNAMENT (TGT) TERHADAP BERPIKIR KRITIS DITINJAU DARI KREATIVITASBELAJAR SISWA - Utomo, Susilo Setyo; Yutmini, Sri; Mulyoto, M. (Sebelas Maret University (UNS), 2016)
The objective of research was to find out: 1) the effect of GI and TGT learning method types on the student’s critical thinking in history learning in Public Senior High Schools in Pati Regency, 2) the effect of learning creativity on the student’ critical learning in history learning in Public Senior High Schools in Pati Regency, and 3) the effect of interaction between learning method and creativity level on the student’ critical learning in history learning in Public Senior High Schools in Pati Regency. The research method used in this research was an experimental method with a 2 x 2 factorial design. Based on the result of research, it could be concluded: (1) There was a significant effect of GI and TGT method uses on the student’s critical thinking in history learning. The result of research showed that the student’s critical thinking ability in history learning using GI method, the students obtained better mean score (mean = 71.83) than that of those using TGT method did (mean = 65.36). (2) There was a significant effect of high and low student learning creativity on the student’s critical thinking in history learning. The students with high creativity had higher mean score of critical thinking (mean = 72.03) than those with low critical thinking had (mean = 64.93). (3)There was no significant interaction of effect between learning method and student creativity to improve the student’s critical thinking ability in history learning.